2017
DOI: 10.17556/erziefd.285046
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Öğretmeni Adaylarının Kitap Okuma Alışkanlıklarının Genel Öz Yeterlikleri Üzerindeki Etkisi

Abstract: This study aimed to determine whether a significant difference existed between gender and grades, and reading habit and general self-efficacy of preservice Turkish teachers. This study was conducted as a mixed methods research. Qualitative and quantitative data were used in the study, and a holistic approach was implemented. The sample of this study included 184 preservice teachers studying at the first, second, third, and fourth grades in Kilis 7 Aralik University. The "Attitude Related to Reading Habit Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, it was found that the results of the study were similar to the results of our study. Biçer and Alan (2017) examined the relationship between book reading habits and self-efficacy of prospective Turkish teachers and found that there was a positive and moderate relationship between book reading habits and self-efficacy. According to the results of this study, it can be suggested that individuals with high level of book reading habits also have high self-efficacy levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that the results of the study were similar to the results of our study. Biçer and Alan (2017) examined the relationship between book reading habits and self-efficacy of prospective Turkish teachers and found that there was a positive and moderate relationship between book reading habits and self-efficacy. According to the results of this study, it can be suggested that individuals with high level of book reading habits also have high self-efficacy levels.…”
Section: Discussionmentioning
confidence: 99%
“…When studies, which were carried out with pre-service teachers upon reading skills, were examined in the body of literature, they are generally observed to be focused on reading success, reading habit and attitude towards reading. Akkaya and İşçi (2018); Tekşan and Çinpolat (2018); Sarikaya (2018); Akbaba (2017); Işık and Demir (2017); Şengül Bircan (2017); Yangil (2017); Biçer and Alan (2017); Durmuş and Baş (2016); Koçak, Çermik, Polat and Şahin (2016); Ulutaş (2016); İlgar, İlgar and Topaç (2015); Akın (2015); Demir (2015); Koçak, Kurtlu, Ulas and Epçapan (2015); Özdemir, Özdemir and Kaya (2015); Gür (2014); Çetinkaya Edizer (2014); Karakuş and Baki (2014), Kalyoncu (2013); Kuzu (2013); Arı and Demir (2013) can be given as examples to these studies which were carried out during the last five years.…”
Section: Introductionmentioning
confidence: 99%